Bohater mityczny w Matce Ziemi Piotra Złotorowicza - Rojek, Patrycja (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2017)
In his etude Mother Earth Piotr Złotorowicz forms the narrative around the mythical hero. The main character Maciek gains the entirety of mythical fulfi llment due to being shaped by (1) space of the execution of the film narration’s subject (indicated by the opposition of home area and garden area), (2) space around him (indicated by sublimed functioning of touch), (3) inability to identify with his own community (indicated by rejecting the butchery tradition of his family), (4) inability to act different than how it was shown (indicated by numerous similarities to Jesus Christ).